2019
DOI: 10.23978/inf.83315
|View full text |Cite
|
Sign up to set email alerts
|

The aspect of time in online health information behaviour

Abstract: Temporal structures and rhythmicity are universal phenomena and affect all aspects of life, including dynamic processes like health and well-being that change over time. Health related issues and threats trigger health information behaviour, a majority of which happens online and thus leaves digital traces behind. This study analyses the temporal variations and rhythmicity of health information behaviour through the action of online posting in a large Finnish discussion forum, Suomi24. The findings in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…Negative emotional experience or uncertainty will trigger people's information needs (Ruthven et al, 2018), and information needs will further direct information behavior. Tana et al (2020) found that online information behavior related to depression varies with time: important daily, weekly, and seasonal peaks can be detected. In addition, studies have found that the disclosure of celebrity depression information can encourage people to seek depression‐related information (Francis, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Negative emotional experience or uncertainty will trigger people's information needs (Ruthven et al, 2018), and information needs will further direct information behavior. Tana et al (2020) found that online information behavior related to depression varies with time: important daily, weekly, and seasonal peaks can be detected. In addition, studies have found that the disclosure of celebrity depression information can encourage people to seek depression‐related information (Francis, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%